Observation of single phonon-mediated quantum transport in a silicon single-electron CMOS single-atom transistor by RMS noise analysis. (18th November 2020) - Bigoni, Stefano; Tagliaferri, Marco L. V.; Tamascelli, Dario; Strangio, Sebastiano; Bez, Roberto; Organtini, Paolo; Ferrari, Giorgio; Prati, Enrico
Abstract: We explore phonon-mediated quantum transport through electronic noise characterization of a commercial CMOS transistor. The device behaves as a single electron transistor thanks to a single impurity atom in the channel. A low noise cryogenic CMOS transimpedance amplifier is exploited to perform low-frequency noise characterization down to the single electron, single donor and single phonon regime simultaneously, not otherwise visible through standard stability diagrams. Single electron tunneling as well as phonon-mediated features emerges in rms-noise measurements. Phonons are emitted at high frequency by generation-recombination phenomena by the impurity atom. The phonon decay is correlated to a Lorentzian 1/ f 2 noise at low frequency.